Circum‐Arctic mantle structure and long‐wavelength topography since the Jurassic. Issue 10 (6th October 2014) - Shephard, G. E.; Flament, N.; Williams, S.; Seton, M.; Gurnis, M.; Müller, R. D.
Abstract The circum‐Arctic is one of the most tectonically complex regions of the world, shaped by a history of ocean basin opening and closure since the Early Jurassic. The region is characterized by contemporaneous large‐scale Cenozoic exhumation extending from Alaska to the Atlantic, but its driving force is unknown. We show that the mantle flow associated with subducted slabs of the South Anuyi, Mongol‐Okhotsk, and Panthalassa oceans have imparted long‐wavelength deflection on overriding plates. We identify the Jurassic‐Cretaceous South Anuyi slab under present‐day Greenland in seismic tomography and numerical mantle flow models. Under North America, we propose the "Farallon" slab results from Andean‐style ocean‐continent convergence around ~30°N and from a combination of ocean‐continent and intraoceanic subduction north of 50°N. We compute circum‐Arctic dynamic topography through time from subduction‐driven convection models and find that slabs have imparted on average <1–16 m/Myr of dynamic subsidence across the region from at least 170 Ma to ~50 Ma. With the exception of Siberia, the main phase of circum‐Arctic dynamic subsidence has been followed either by slowed subsidence or by uplift of <1–6 m/Myr on average to present day. Comparing these results to geological inferences suggest that subduction‐driven dynamic topography can account for rapid Middle to Late Jurassic subsidence in the Slave Craton and North Slope (respectively, <15 and 21 m/Myr, between 170 and 130 Ma) and for dynamic subsidence (<7 m/Myr, ~170–50 Ma) followed by dynamic uplift (<6 m/Myr since 50 Ma) of the Barents Sea region. Combining detailed kinematic reconstructions with geodynamic modeling and key geological observations constitutes a powerful tool to investigate the origin of vertical motion in remote regions.